OPINI GOING CONCERN : DAMPAK UKURAN PERUSAHAAN, FINANCIAL DISTRESS, REPUTASI AUDITOR DAN OPINI AUDIT TAHUN SEBELUMNYA - Utami, Wahyu Indah; Khikmah, Siti Noor; Farida (JURNAL EKONOMI, 2022)
Going concern opinion is the auditor’s opinion, that there is a material uncertainty related to events or conditions, either individually or collectively, which may cause significant doubts about the entity’s ability to continue as a going concern. This study aims to examine the impact of firm size, financial distress, auditor reputation, and previous year’s audit opinion on going concern opinion. The population of this study is the manufacturing sector companies listed on the Indonesa Stock Exchange for the 2018-2020 period. The sampling technique used in this study used purposive sampling and obtaines a sample of 33 companies. The data in this study is secondary data. Hypothesis testing was performes using logistic regression analysis. The results showed that the firm size variable had a negative effect on the going concern opinion. Financial distress and the previous year’s audit opinion have a positive effect on the going concern audit opinion acceptance. Whilethe reputation of auditor does not effect the going concern opinion